1939
DOI: 10.1021/ie50351a014
|View full text |Cite
|
Sign up to set email alerts
|

Electrical Insulating Materials

Abstract: As part of a study to determine which of the types of products that may be formed by the service degradation of insulating oils cause serious dielectric losses in insulating oils at 60 cycles and which do not, properties of systems composed of liquid paraffin and a cupric or lead soap of the following acids have been investigated: 1,10-hydroxystearic, stearic, palmitic, myristic, lauric, capric, pelargonio, caprylic, cyclohexanecarboxylic, undecylenic, erucic, and abietic acids. In the preparation of these soa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

1940
1940
2013
2013

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 16 publications
(7 citation statements)
references
References 7 publications
0
7
0
Order By: Relevance
“…Inasmuch as all the systems with higher power factors than solutions containing equimolecular proportions of acid or base became heterogeneous upon cooling (whereupon their power factors increased), an alternative explanation seems possible. Previous work with soaps (8) and with oxidation products (11) showed that systems appearing to be homogeneous but becoming visually heterogeneous at lower temperatures often exhibit dielectric behaviors resembling those of heterogeneous rather than of homogeneous systems. Tri-n-butylamine From consideration of the data obtained it is believed that, although the presence of sufficiently high proportions of soluble salts resulting from reaction between nitrogen bases and carboxylic acids can cause high power factors in insulating oils, the presence of such compounds in proportions equivalent to the low nitrogen content of insulating oils does not appreciably affect the power factors of the solutions.…”
Section: Organic Salts Of Nitrogen Basesmentioning
confidence: 99%
See 1 more Smart Citation
“…Inasmuch as all the systems with higher power factors than solutions containing equimolecular proportions of acid or base became heterogeneous upon cooling (whereupon their power factors increased), an alternative explanation seems possible. Previous work with soaps (8) and with oxidation products (11) showed that systems appearing to be homogeneous but becoming visually heterogeneous at lower temperatures often exhibit dielectric behaviors resembling those of heterogeneous rather than of homogeneous systems. Tri-n-butylamine From consideration of the data obtained it is believed that, although the presence of sufficiently high proportions of soluble salts resulting from reaction between nitrogen bases and carboxylic acids can cause high power factors in insulating oils, the presence of such compounds in proportions equivalent to the low nitrogen content of insulating oils does not appreciably affect the power factors of the solutions.…”
Section: Organic Salts Of Nitrogen Basesmentioning
confidence: 99%
“…To minimize the number of variables, the authors prepared numerous systems consisting of liquid paraffin and one or more highly purified compounds selected to represent types of products that might be found in or formed in insulating oils during deterioration, and investigated the power factors and related properties of these systems. The systems investigated were prepared to simulate deteriorated oils containing oilsoluble oxidation products (IS, IS), sparingly soluble oxidation products (11), copper and lead soaps such as are formed by oxidation of oils in contact with these metals (8), and products resulting from corona discharge on insulating oils (16). For concentrations of contaminants that could reasonably be expected to be formed in service, significantly high power factors have been found only when one component of the contaminant is by itself incompletely soluble in the oil.…”
mentioning
confidence: 99%
“…This involves treating an aqueous solution of the appropriate sodium or potassium soap with a solution of a metal salt, filtering off the precipitate, washing with ethanol and acetone and drying. Copper and lead dodecanoates and octadecanoates can be obtained from the acetates (77); zinc, cadmium, magnesium and aluminum, etc., carboxylates can be obtained from the corresponding chlorides (65,87).…”
Section: Preparation Of Heavy Metal Soaps a Soaps Based On Carboxylic...mentioning
confidence: 99%
“…In other cases additives have been selected to resemble certain properties of deterioration products whose structures are unknown. Up to the present the classes of additives have been: oil-soluble oxidation products in oil (11) and in impregnated paper (IS); copper and lead soaps (7); sulfur and nitrogen compounds (8); and products resulting from subjecting oil to corona discharge (IS) in oil.…”
Section: Additive Studiesmentioning
confidence: 99%